Dexmedetomidine: a real-world safety analysis based on FDA adverse event reporting system database - Shuai, Yichun; Chen, Zhe; Wan, Qiaoqian; Wu, Jinzheng; Wang, Xin (Frontiers in Pharmacology, 2024)
Objective: Using the FDA adverse event reporting system (FAERS) database to analyze the safety profile of Dexmedetomidine and provide guidance for clinical application. Methods: Data from the FAERS database from the first quarter of 2004 to the third quarter of 2023 were collected. Reporting odds ratio (ROR), the proportional reporting ratio (PRR), and the Bayesian confidence propagation neural network (BCPNN) were employed to detect and assess adverse events associated with Dexmedetomidine. Results: A total of 1910 reports of Dexmedetomidine as the primary suspect drug were obtained. After screening, 892 preferred terms were obtained, including 52 new preferred terms not mentioned in the drug insert. The common adverse events of Dexmedetomidine include bradycardia, cardiac arrest, hypotension, diabetes insipidus, arteriospasm coronary and agitation. Notably, cardiac disorders exhibited the highest number of reports and the highest signal intensity in the system organ class. Among the new preferred terms, those with high signal intensity include transcranial electrical motor evoked potential monitoring abnormal, acute motor axonal neuropathy, trigemino-cardiac reflex, glossoptosis, floppy iris syndrome, phaeochromocytoma crisis, postresuscitation encephalopathy and diabetes insipidus. Conclusion: This study mined and evaluated adverse events associated with Dexmedetomidine and also identified new adverse events. This could help alert clinicians to new adverse events not mentioned in the drug inserts, reducing the risk of drug.